2010
DOI: 10.1590/s1413-81232010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Perdas de vitamina C em hortaliças durante o armazenamento, preparo e distribuição em restaurantes

Abstract: Perdas de vitamina C em hortaliças durante o armazenamento, preparo e distribuição em restaurantesVitamin C loss in vegetables during storage, preparation and distribution in restaurants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2
9

Year Published

2010
2010
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
0
7
2
9
Order By: Relevance
“…Although Table 3 shows different content and retentions for AA, DHA, vitamin C, lycopene and b-carotene, these differences are not statistically significant. In a study comparing the AA losses in tomato after each processing stage in restaurants, the final retention was around 50% (Moraes et al 2010), much lower than those observed in the present study (about 85%). It is possible that in the present study the n.s., not significant.…”
Section: Vitamin C and Carotenoid Retention And Handling Practicescontrasting
confidence: 89%
See 1 more Smart Citation
“…Although Table 3 shows different content and retentions for AA, DHA, vitamin C, lycopene and b-carotene, these differences are not statistically significant. In a study comparing the AA losses in tomato after each processing stage in restaurants, the final retention was around 50% (Moraes et al 2010), much lower than those observed in the present study (about 85%). It is possible that in the present study the n.s., not significant.…”
Section: Vitamin C and Carotenoid Retention And Handling Practicescontrasting
confidence: 89%
“…It is possible that in the present study the non-addition of seasoning resulted in lower losses, despite exposure to light, room temperature and oxygen. In a study comparing the AA losses in tomato after each processing stage in restaurants, the final retention was around 50% (Moraes et al 2010), much lower than those observed in the present study (about 85%). The greatest percentage loss in restaurants occurred during storage, and time being more influential than temperature during storage.…”
Section: Vitamin C and Carotenoid Retention And Handling Practicescontrasting
confidence: 89%
“…The difference in the ascorbic acid content of GT and BTs could have resulted from the fermentation processing of black teas. In a recent study by Moraes et al [24] a decline in the ascorbic acid content of vegetables was also observed with different processing techniques. Furthermore, taking into consideration that the major constituent of the ADT used in this study is white tea; the significant difference in ascorbic acid between both could be a result of the maturity of the leaves.…”
Section: Discussionmentioning
confidence: 86%
“…Na casca da cenoura, observou-se perdas de 42,55% para o tratamento a vapor, e de 4,21% para o tratamento com o uso do microondas em relação ao vegetal cru, sendo verificado então que os tratamentos mais efetivos na manutenção dos teores de ácido ascórbico foram aqueles em que a casca foi submetida ao cozimento no vapor e microondas. Moraes et al (2010) observaram grande redução de vitamina C na cenoura após cocção, a mesma foi colocada para cozinhar antes da água entrar em ebulição e o tempo foi superior ao necessário, elevando as chances de perdas por lixiviação e pelo calor. Além disso, a cenoura foi colocada para cozinhar já picada, o que agrava a perda de vitaminas.…”
Section: Resultsunclassified